2016
DOI: 10.1590/s0100-83582016340100009
|View full text |Cite
|
Sign up to set email alerts
|

Weed Community in a Raw Sugarcane Renovation Area Submitted to Different Soil Managements

Abstract: -The objective of this study was to evaluate the weed community in a raw sugarcane renovation area with three soil managements and peanut sowing in succession. The experiment was conducted during the 2007/08 season on a raw sugarcane area harvested without prior burning in the last five cuts. A randomized block design with treatments arranged in a split plot and arranged in four replications was used. The main treatments consisted of three cropping systems: conventional tillage, minimum tillage and direct plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…These data corroborate results reported by this study regarding the lower density of Oryza sativa in this system ( Table 2). Systems that maintain soil cover, such as minimum tillage and direct sowing, affect the development of gramineous plants (SOARES et al, 2016). Infestation by these species virtually disappears when soil management is conservative.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These data corroborate results reported by this study regarding the lower density of Oryza sativa in this system ( Table 2). Systems that maintain soil cover, such as minimum tillage and direct sowing, affect the development of gramineous plants (SOARES et al, 2016). Infestation by these species virtually disappears when soil management is conservative.…”
Section: Resultsmentioning
confidence: 99%
“…They decreased up to S5 from 164 (average S1 and S2) to 79 (average S3, S4 and S5) plants m -2 , depending on the increase in the system diversification (Table 3), showing the importance of crop rotation to weed management. Studies of direct sowing fields with Arachis hypogaea L. crop rotation, in which Cyperus rotundus L. stood out among the weeds, showed that conservative soil management and crop rotation mitigated problems resulting from this species (SOARES et al, 2016). This result may be attributed to the fact that some species, such as C. rotundus, are more sensitive to light, which interferes in the germination of their propagules (ALBUQUERQUE et al 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A espécie Ipomoea hederifolia esteve presente em todos os tratamentos, enquanto a espécie Coniza bonariensis foi encontrada apenas no tratamento 1 e, Mucuna aterrima apenas no tratamento 4 e Diodella teres e Setaria parviflora foram exclusivas ao tratamento 2. De maneira geral as áreas de plantio direto apresentam menor número de plantas daninhas e maior riqueza de espécies, enquanto no plantio convencional espécies problemáticas costumam sobressaírem-se (SOARES et al,2016). Na Tabela 5 é possível observar os dados de número de plantas daninhas por m² e massa seca de plantas daninhas por m².…”
Section: Resultado E Discussãounclassified
“…Weed communities are affected by various factors, including climate, soil type, soil weed seed bank, planting and production systems adopted, and crop development (Albuquerque et al, 2012). Changes in the soil management system generally influence weed density and diversity (Soares et al, 2016). Phytosociological surveys are useful tools for understanding the dynamics of weed species and their interaction with management systems and agricultural practices (Carvalho and Pitelli, 2012;Concenço et al, 2013).…”
mentioning
confidence: 99%